Waqf financing expenditure and its impact on government debt - Azrai Azaimi Ambrose, Azniza Hartini; Aslam, Mohamed; Hanafi, Hanira (European Journal of Islamic Finance, 2019)
The Malaysian debt has been under scrutiny since the 1Malaysia Development Berhad (1MDB) scandal; placing pressure on the research for sustainable debt. The purpose of this article is to forecast the impact of waqf (Islamic pious foundation) financing expenditure on federal government debt in Malaysia. It is to ascertain whether waqf can be an alternative solution to government debt reduction. To perform this, the Neoclassical Dynamic Stochastic General Equilibrium (DSGE) model is adopted. The theoretical framework is developed by considering the history, tradition, culture, and political influence of waqf primarily in Muslim majority countries. It was also inspired by the European third sector framework. The result shows that federal government debt can be reduced when waqf finances federal government expenditure. This has several implications. For one, this study revives the cohesive government-waqf role in providing pure and mixed public goods without depending solely on government expenditure. It highlights the fact that these shared role has an impact of reducing government debt. The result also inadvertently provides evidence of a significant third sector role on public finance dynamics. As a matter of fact, this study is one of very few quantitative attempts in illustrating how waqf interacts with the economy and its impact on government debt.